Breakfast Types Are Associated with Adolescents' IQ and Academic Achievement (P18-103-19). (13th June 2019) - Liu, Jianghong; Wu, Lezhou; Hanlon, Alexandra; Tien, Joyce; Um, Phoebe; Dickerman, Barbra; Irving, Sharon; Shi, Zumin; Compher, Charlene
Abstract: Objectives: Research has documented that frequent breakfast consumption is associated with better cognition. However, the relationship between breakfast type and cognitive functioning is lesser known. In this study, we examined both breakfast type and consumption frequency in relation to IQ and academic achievement in a sample of 12-year-old Chinese schoolchildren. Methods: Participants included 835 12-year-old children from the China Jintan Cohort Study. Breakfast habits, food types, and intake frequency were assessed through self-administered nutrition questionnaires. The types of foods measured included fruits/vegetables, grain/rice, meat/egg, dairy products, and soy products. IQ was measured with the Chinese version of the Wechsler Intelligence Scale for Children. Standardized academic achievement was collected through school reports. Multivariate general linear modeling was implemented for data analysis. Results: More frequent breakfast consumption of grain/rice and meat/egg (6–7 days per week) was significantly associated with higher verbal, performance, and full scale IQs, by 3.562, 3.687, and 4.559 points, respectively (all P  < 0.05), compared with rare grain/rice intake (0–2 days per week). Regular meat/egg breakfast consumption appeared to facilitate academic achievement (6–7 vs. 0–2 d/w, mean difference = 0.232, P  = 0.043). Interestingly, frequent consumption of fruit/vegetables and dairy products did not affect cognitive functioning. Furthermore, an intermediate frequency (3–5 d/w) showed better verbal IQ and academic achievement. A dose-response relationship showed that even after adjustment for up to nine covariates, those who ate breakfast 6–7 days per week tended to have a higher verbal IQ score of 6.760 ( P  = 0.017) and a higher average academic achievement score of 0.831 ( P  < 0.001), than those who rarely ate breakfast (0–2 d/w). Conclusions: Our study shows that frequent consumption of grain/rice and meat/egg for breakfast may have positive associations with cognitive functioning in adolescents. Nevertheless, inference cannot be drawn from this cross-sectional analysis. Future studies should assess the long-term effects of breakfast type on cognitive abilities. Funding Sources: National Institute of Environmental Health Sciences/National Institutes of Health (R01-ES-01, 8858, K02-ES-01, 9878, and K01-ES015877).